2016
DOI: 10.1073/pnas.1521494113
|View full text |Cite
|
Sign up to set email alerts
|

Clouds at Barbados are representative of clouds across the trade wind regions in observations and climate models

Abstract: Trade wind regions cover most of the tropical oceans, and the prevailing cloud type is shallow cumulus. These small clouds are parameterized by climate models, and changes in their radiative effects strongly and directly contribute to the spread in estimates of climate sensitivity. This study investigates the structure and variability of these clouds in observations and climate models. The study builds upon recent detailed model evaluations using observations from the island of Barbados. Using a dynamical regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 64 publications
2
50
0
Order By: Relevance
“…The width of these layers is similar to the AIRS 700 and 925 hPa temperature and specific humidity weighting functions. Even though the RICO observations do not fall within any of the four regions listed in Table 1, Medeiros and Nuijens (2016) show that the observational site is applicable to the trade regime as a whole across the globe. Thus our approach for the remainder of the investigation is to determine if similar relationships shown in Nuijens et al (2009) exist in cumulus for the regions listed in Table 1.…”
Section: Relating Meteorology and Microphysical Processesmentioning
confidence: 76%
See 1 more Smart Citation
“…The width of these layers is similar to the AIRS 700 and 925 hPa temperature and specific humidity weighting functions. Even though the RICO observations do not fall within any of the four regions listed in Table 1, Medeiros and Nuijens (2016) show that the observational site is applicable to the trade regime as a whole across the globe. Thus our approach for the remainder of the investigation is to determine if similar relationships shown in Nuijens et al (2009) exist in cumulus for the regions listed in Table 1.…”
Section: Relating Meteorology and Microphysical Processesmentioning
confidence: 76%
“…Therefore, the assumption that constant RH might hold across the diversity of subtropical cloud regimes with a changing climate is likely not valid. Medeiros and Nuijens (2016) showed that the RH gradient between the MBL and lower free troposphere is widely variable among the CMIP5 models within the trade cumulus regime. Therefore, further examination of cloud variability and the vertical structure of RH with present-day satellite and reanalysis observations is warranted.…”
Section: Introductionmentioning
confidence: 99%
“…First, shallow cumuli are prominent in this area, especially during winter (Norris 1998;Nuijens et al 2014). Second, the cloudiness in the vicinity of Barbados is representative of clouds across the whole tradewind regions of the tropical ocean, both in models and in observations (Medeiros and Nuijens 2016). Finally, it anchors the measurements to the extensively instrumented Barbados Cloud Observatory which has been monitoring clouds continuously since 2010, and allows it to benefit from the legacy of the NARVAL series of flight campaigns organized in the area in the last few years ).…”
mentioning
confidence: 91%
“…This site has been selected for several reasons. First, Medeiros and Nuijens () show that the climatological conditions and the cloud properties measured at BCO are representative of the Trades. Second, the cloud fields of this region have been widely investigated in field campaigns (e.g., Nitta & Esbensen, ; Rauber et al, ) and in model studies (e.g., Nuijens et al, ; Siebesma & Cuijpers, ; Vanzanten et al, ).…”
Section: Radiative‐advective Equilibrium In the Tradesmentioning
confidence: 99%
“…We restrict our analysis to the dry season , defined as the period between January and April, following Brueck et al (). The reason for this choice is twofold: on the one hand, the focus of this study is on BL clouds, which are dominant in the dry season (Medeiros & Nuijens, ); on the other, the SCM is not ideally suited for simulating deep convection because, in its standard setup, it does not include the direct feedback of the deep convection on the dynamics. More complex setups allowing for the deep cumulus regime, such as the application of the weak temperature gradient method (e.g., Ruppert, ; Sobel et al, ), will be considered in future work.…”
Section: Radiative‐advective Equilibrium In the Tradesmentioning
confidence: 99%